Peran Manajemen Higiene Industri dalam Meningkatkan Keselamatan dan Kesehatan Kerja - Pangaribuan, Muhammad Husin; Shafa Kirana; Slhella Ramadhayanti; Hasibuan, Abdurrozzaq (Publikasi Inspirasi Indonesia, 2026)
Rapid industrial development demands a more rigorous implementation of Occupational Safety and Health (OHS) to proctect workers from potential physical,chemical,biological,and ergonomic hazards.This study aims to examine the role of industrial hygiene management in improving OHS through a desk study approach analyzing literature from the past ten years.the results indicate that industrial hygiene management plays a crucial role in early identification,risk assesment,and a hazard control through a systematic hierarchy of controls.Effective implementation of hygiene management has been proven not only to prevent occupational diseases and accidents but also directly increase workforce productivity and provide economic benefits to companies through work effeciency and reduced compensation costs,However,implementation in the field still faces challenges such as loe worker awarness,limited resources,and weak management commitment.Therefore,strong management support,adequate facilities,and on going monitoring are key to successfully creating an optimal safety culture in the workplace.